2021
DOI: 10.3892/etm.2021.10324
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG11 aggravates cell proliferation and migration in triple‑negative breast cancer via sponging miR‑2355‑5p and targeting CBX5

Abstract: Triple-negative breast cancer (TNBC) is one of the most common malignances worldwide. Concurrently, the incidence of TNBC has continued to rise in recent years. It is reported that long non-coding RNAs (lncRNAs) are involved in biological processes in numerous cancers including TNBC. Small nucleolar RNA host gene 11 (SNHG11) has already been studied and reported in some cancers. However, the role of SNHG11 in TNBC remains unknown. RT-qPCR was used to measure gene expression in the current study. CCK-8, colony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Snhg11 has been proposed to act as a microRNA (miRNA) sponge [44,45]. In line with this role, the genes that are downregulated upon Snhg11 knockdown are highly enriched in targets of miRNAs predicted to bind Snhg11.…”
Section: Aso-mediated Knockdown Of Snhg11 In Vivo Leads To Trisomic-l...mentioning
confidence: 99%
“…Snhg11 has been proposed to act as a microRNA (miRNA) sponge [44,45]. In line with this role, the genes that are downregulated upon Snhg11 knockdown are highly enriched in targets of miRNAs predicted to bind Snhg11.…”
Section: Aso-mediated Knockdown Of Snhg11 In Vivo Leads To Trisomic-l...mentioning
confidence: 99%
“…CBX5 silencing can inhibit cell proliferation and metastasis, while overexpression promotes the proliferation and metastasis of TNBC cells, and can be regulated by miR-2335-5p/lncRNA SNHG11 signaling pathway. 33 These results together indicate that CBX5 plays a carcinogenic role in many cancers including BC.…”
Section: Discussionmentioning
confidence: 80%
“…XIST enhanced the chemoresistance and tumorigenesis of CRC by adsorbing miR-125b-2-3p and elevating WEE1 [24]. Previous studies reported that SNHG11 acted as a contributor in triple-negative breast cancer [25], hepatocellular carcinoma [26] and pancreatic carcinoma [27] through different pathways. Moreover, SNHG11 was able to exacerbate CRC malignancy [28,29].…”
Section: Discussionmentioning
confidence: 99%